A novel selective medium Sucrose-Bacitracin agar 10 for accurate isolation and identification of Streptococcus mutans - Yuwen Fang; Qizhao Ma; Wei Zhao; Nian Liu; Lei Cheng; Jing Chen; Jing Zou (BMC Oral Health)
Abstract Background To develop and evaluate Sucrose-Bacitracin agar with 10% sucrose (SB-10), a novel selective medium designed to enhance the isolation and identification of Streptococcus mutans, a key cariogenic pathogen in dental caries. Methods SB-10 was compared to Mitis Salivarius Bacitracin agar with 20% sucrose (MSB-20) for its ability to support S. mutans growth, promote distinctive colony morphology, and differentiate it from other oral bacteria. Sugar particle formation was assessed using wild-type and mutant strains of S. mutans lacking glucosyltransferases B and C (GtfB and GtfC). Liquid chromatography was performed to characterize the sugar particles around colonies. The specificity and clinical utility of SB-10 were further assessed by culturing clinical saliva samples and confirming S. mutans colonies via 16S rRNA sequencing. Results SB-10 supported robust S. mutans growth with larger colonies and distinctive sugar particle formation compared to MSB-20. GtfB and GtfC were essential for sugar particle deposition around colonies. SB-10 demonstrated high specificity by suppressing the growth of non-target oral bacteria and accurately isolating S. mutans from clinical saliva samples, with all colonies confirmed as S. mutans via 16S rRNA sequencing. Conclusions SB-10 is a novel selective medium that enhances the isolation and identification of S. mutans, characterized by unique sugar particles deposition and colony morphology.